Maturational patterns in right ventricular strain mechanics from the fetus to the young infant. (February 2019) - Erickson, Collin T.; Levy, Philip T.; Craft, Mary; Li, Ling; Danford, David A.; Kutty, Shelby
Abstract: Aim: To test the hypothesis that right ventricular (RV) function has age-specific patterns of development, we tracked the evolution of RV strain mechanics by 2D-speckle tracking echocardiography (2DSTE) in healthy subjects from mid-gestation through one year of age. Methods: We conducted a prospective longitudinal echocardiography study in 50 healthy subjects at five time periods across gestation (16–20 weeks, 21–25 weeks, 26–30 weeks, 31–35 weeks, and 36–40 weeks) and four time periods following delivery (1 week, 1 month, 6 months, and 1 year of age). We characterized RV function by measuring RV global and free wall longitudinal strain and systolic strain rate, and segmental longitudinal strain at the apical-, mid-, and basal- ventricular levels of the free wall. Possible associations of gestational age, postnatal age, estimated fetal weight, body surface area, gender, and heart rate on strain were investigated. Results: The magnitudes of RV global and free wall longitudinal strain and global strain rate were decreased throughout gestation (p < 0.05 for all). Following birth, the magnitudes of all measures increased from one week through one year (p < 0.001 for all). RV segmental longitudinal strain maintained a base-to-apex gradient (highest-to-lowest) from mid-gestation through one year (p < 0.001). There was no significant difference in strain patterns based on gender or hear rate. Conclusion: The maturational patterns of RV strain are gestational- and postnatal age- specific. With accepted physiological maturation patterns in healthy subjects, these myocardial deformation parameters can provide a valid basis that allows comparison between health and disease. Highlights: Myocardial strain imaging is validated method to characterize right ventricular function in fetuses and neonates. Major hemodynamic alterations of cardiovascular transition distinguish the fetal period from the postnatal period. This study establishes clinically relevant patterns of RV strain mechanics from early gestation through the one year. Developmental RV strain mechanics are gestational- and postnatal age- specific.